Možnost množičnega/obsežnejšega razmnoževanja pravega kostanja (Castanea Mill sp.) z zelenimi potaknjenci - Osterc, Gregor (Gozdarski vestnik, 2026)
Beekeeping also has an unique character in Slovenia and is therefore of importance throughout the country. The sweet chestnut poses a particular challenge for nursery management due to its recalcitrance in vegetative reproduction. Sexual propagation, based on the use of seeds, is consistently possible and has long been the standard propagation method for this species in horticulture (not only in forestry). However, sexual propagation is associated with various problems, from the poorer germination of the seeds in some years to the difficult stratification or short-term storage and the impossibility of safe long-term storage of the seeds. Asexual propagation has become widespread in fruit growing practice in recent decades, with grafting being used as an obvious method. However, especially when trees from crosses between species are grafted onto seedlings of one species, it leads to incompatibilities and even the death of the grafted trees. For this reason, the possibility of successfully propagating sweet chestnut trees using leafy cuttings has long been discussed, but to date, despite several attempts, there is no successful method that also has economic potential.
Keywords: adventitious rooting system; ARS; asexual propagation; cuttings of sweet chestnut; fog system; megljenje; nadomestni koreninski sistem; nespolno razmnoževanje; NKS; potaknjenci domačega kostanja